Association Between Parkinson’s Disease and Melanoma: Putting the Pieces Together - Ye, Qing; Wen, Ya; Al-Kuwari, Nasser; Chen, Xiqun (Frontiers in Aging Neuroscience, 2020)
Patients with Parkinson’s disease (PD) generally have reduced risk of developing many types of cancers, except melanoma - a malignant tumor of melanin-producing cells in the skin. For decades, a large number of epidemiological studies have reported that occurrence of melanoma is higher than expected among subjects with PD, and occurrence of PD is reciprocally higher than expected among patients with melanoma. More recent epidemiological studies further indicated a bidirectional association, not only in the patients themselves but also in their relatives. This association between PD and melanoma offers a unique opportunity to understand PD. Here we summarize epidemiological, clinical, and biological evidence in regard to shared risk factors and possible underlying mechanisms for these two seemingly distinct conditions.